EXISTENCE OF SYSTEMS OF GENERALIZED VECTOR QUASI-EQUILIBRIUMS IN PRODUCT FC-SPACES - Sombut, K.; Plubtieng, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper, three classes of systems of generalized vector quasi-equilibrium problems are introduced and studied in product FCspaceswithoutconvexity structure. We prove some new equilibrium existence theorems for three classes of systems of generalized vector quasi-equilibrium problems in noncompact product FCspaces.These results improve and generalize some recent results in literature to product FCspaceswithout any convexity structure.